Student’s Attitudes, Study Habits, and Academic Performance in Science Using Self-Learning Modules - Mutya, R. C.; Alcantara, G. A.; Sala, A. M. V.; Carascal, I. C.; Terana, C. C.; Presbitero, M. S. C. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study examined students’ attitudes, study habits, and academic performance in science using self-learning modules. This type of research is a descriptive-correlational design utilizing a standardized survey questionnaire. The research subjects were 174 secondary students in a public school. Data analysis used descriptive techniques, Pearson’s correlation coefficient, and multiple regression analysis. Findings revealed that students have a positive attitude toward science and have fair study habits. Students are very satisfactory in time management, concentration, goal setting preparation and follow-up, comprehension, and use of resources. Hence, students positively perceive that Science teachers in distance learning using the SLMs make science enjoyable and present material. This study concluded that using the self-learning modules, students have positive attitudes toward science, very satisfactory study habits, and most of the students have satisfactory academic performance. No correlation was found between students’ academic performance and attitudes toward science using self-learning modules and between academic performance and study habits in science. However, a positive correlation existed between students’ attitudes toward science and study habits using self-learning modules. This study will have important implications for education in the new normal, including improving student engagement and motivation by understanding the relationship between attitudes, study habits and academic performance will help educators to design self-learning modules that support students in developing positive attitudes, study habits, leading to improved engagement and motivation.